Improved angle accuracy of tibial plateau osteotomy for total knee arthroplasty using tibial mechanical axis skin-mapping - He, Peiheng; Huang, Shuai; Liu, Yong; Li, Xing; Xu, Dongliang (Frontiers in Surgery, 2023)
Background: Tibial crest is often referred to anatomic landmark for tibia plateau osteotomy (TPO) in total knee arthroplasty (TKA), but it is not so accurate.The purpose of this study was to investigate the errors of the tibial crest as anatomic landmark and present a simple approach to improve the accuracy accuracy of TPO by marking tibia mechanical axis (TMA) on shank skin determined preoperatively according to tibial crest. Methods: This study involves 50 young volunteers and 100 knee osteoarthritic patients for TKA. Middle tibial crest lines (MTCL) were marked on the shank skin and pasted with Kirschner wires. All volunteers and patients were underwent an anteroposterior standing radiographs of lower extremity, which positions were stuck at neutral and external rotation. The angles between MTCL and TMA were measured (angle MA), and the correlations were evaluated. Then TMA was marked on Shank Skin accordong to angle MA and used during TKA. Postoperative outcome was determined by the angle between the vertical tibial component axis (TCA) and TMA. Results: The MTCL had no evident relationship with TMA. A few MTCL were parallel to the TMA.The external rotation angle of the foot significantly changed the relationship between MTCL and TMA. Accuracy of the TPO guided by the TMA marked on shank skin was 0.83°±0.76°. No cases exceeded a 3° error. Conclusion: The MTCL was not equivalent to TMA. The error for TPO can be reduced by preoperatively marking the TMA on the shank skin based on the MTCL.